Age Differences In Emotion Recognition: Task Demands Or Perceptual Dedifferentiation?. Issue 5 (20th October 2017) - Franklin, Robert G.; Zebrowitz, Leslie A.
ABSTRACT: Background/Study Context : Older adults (OA) have consistently shown lower accuracy compared with younger adults (YA) when labeling facial expressions of emotion in multiple choice tasks. However, OA do not show lower accuracy when judging psychological attributes from faces in rating tasks. The authors investigated whether the cognitive demands of multiple choice tasks yields an underestimation of OA emotion recognition ability and whether lower scores by OA in emotion recognition tasks are an instance of age-related dedifferentiated face perception. Methods : Younger and older adults judged the emotions of faces depicting various expressions using (a) a multiple choice task and (b) a rating task with separate scales for each expression. We computed both accuracy scores and an emotion differentiation index, adapted from previous work on neural activation to different stimulus categories. Results : Lower OA performance in emotion recognition do not reflect the cognitive demands of a multiple choice task, since age differences also were shown when assessing emotion expressions on independent rating scales. An index calculating differentiation of the emotion expressions supported the hypothesis that age differences in emotion recognition accuracy may reflect age-related perceptual dedifferentiation. Discussion : Results are consistent with other evidence for perceptual dedifferentiation in OA, including lower OA performance in face recognition tasks, rating faces more similarly to one another on trait dimensions, and less specificity in neural activation to faces.